Challenges in 3D printing of piezoelectric materials. Issue 2 (27th March 2019) - Bodkhe, Sampada; Ermanni, Paolo
Abstract: Three-dimensional printing (3DP), the fastest growing manufacturing community, in a quest to capitalize its principal advantage of customization is exceedingly seeking functional materials. Piezoelectric materials are one such type of functional material desired for their linear electromechanical and thermoelectric behavior. The ability to 3D print piezoelectric material opens up a new demographic of integrated and personalized smart devices serving from aerospace to biomedical applications. Being self-powered further renders them a competing material for devices used in remote locations: inside the human body, and confined and inaccessible spaces. The review evaluates the significance of 3DP structures over their conventionally fabricated counterparts as well as those of 3D structures over 2D and 1D equivalents. Although, 3DP of these materials is successfully attempted using various techniques, there remain concerns in optimizing the function with the form. This review analyzes the current 3DP techniques available for piezoelectric material and addresses the challenges in realizing ready-to-use piezoelectric sensors and applying them in multi-material printing by resolving the issues associated with electrode formation and poling. As all the current characterization techniques are restricted to 2D geometries, we propose a list of potential techniques to efficiently characterize 3D piezoelectric structures. Finally, a road-map is provided to choose an appropriate 3DP technique and the corresponding material system pertaining to a given application.